Seleção de linhagens de feijão para produção, acúmulo e eficiência de uso de fósforo na planta - Mambrin, Ritieli Baptista (2016)
The use of common bean (Phaseolus vulgaris L.) cultivars efficient and responsive to phosphorus use is important for increase grain yield and reduce production cost. Thus, the objectives of this work were: (1) evaluate the response of common bean lines in production of dry matter, grain yield components, and accumulation of phosphorus in the plant under different phosphorus availability; (2) investigate the association between these characters; (3) evaluate the genetic variability of common bean lines as the phosphorus availability; (4) identify efficient lines in phosphorus use and responsive to application of mineral by different indexes. For this, four experiments were carried out in a greenhouse of the Plant Science Department at the Santa Maria Federal University during the years 2013 2015, in a completely randomized design in a sub-sub-divided plot. In the first two experiments the phosphorus concentration tested in the nutrient solution were from 0.5 to 2.3 mmol L-1 as part of the main plot; Perola and IPR88 Uirapurú cultivars were evaluated in the sub-plot, and the growing seasons (fall-winter and spring-summer) in the sub-sub-plot. In the third and four experiments were evaluated the efficiency of phosphorus use and 12 genotypes response the low (0.9 mmol L-1) and high (1.9 mmol L-1) phosphorus concentration in the nutrient solution in two growing seasons. Phosphorus concentration in the nutrient solution from 1.33 to 1.84 mmol L-1 provided higher dry mass of pod at pod filling stage (R8), high dry mass of grains at maturation (R9), and higher number of grains and grain yield, for Pérola and IPR88 Uirapurú cultivars. Phosphorus concentration in the nutrient solution from 1.37 to 1.96 mmol L-1 result in high phosphorus concentration in: leaves at first trifoliate leaf (V4), stem at flowering (R6);,leaves, stem and pods at pod filling (R8), grains at maturation (R9), and high grain yield and phytic acid, in growing seasons (fall-winter and spring-summer). The characters dry mass of the leaves, stem and pods at pod filling stage (R8), dry mass of grains at maturity (R9), number of grains and number of pods are promising for allowing indirect selection. The evaluation of the phosphorus concentration in plant tissues at pod filling stage (R8) is promising and allowing indirect selection for the grain yield in common bean. The L 2225, L 2632, L 2527 and L 2411 lines, stood out due to high production of dry mass of stem in low phosphorus concentration in the culture medium. There is genetic variability among common bean lines studied for dry matter production, grain yield and phosphorus accumulation in tissues. The L 2527 line proved to be efficient and responsive for phosphorus use.